11. Zapisz w postaci sumy algebraicznej.
a) (x - 5)³ + (x+3)³
b) (3x - 1)³ - (2x + 1)³
c) (x + 1⁄2 )³ + (x − 1/2)³
d) (2x + 3)³ - (2x - 3)³​


Odpowiedź :

Odpowiedź:

[tex]a)\ \ 2x^3-6x^2+102x-98\\\\b)\ \ 19x^3-39x^2+3x-2\\\\c)\ \ 2x^3+\frac{3}{2}x\\\\d)\ \ 72x^2+54[/tex]

Szczegółowe wyjaśnienie:

Wykorzystano  wzory skróconego mnożenia

[tex](a-b)^3=a^3-3a^2b+3ab^2-b^3\\\\(a+b)^3=a^3+3a^2b+3ab^2+b^3[/tex]

[tex]a)\ \ (x-5)^3+(x+3)^3=x^3-3x^2\cdot5+3x\cdot5^2-5^3+x^3+3x^2\cdot3+3x\cdot3^2+3^3=\\\\=x^3-15x^2+3x\cdot25-125+x^3+9x^2+3x\cdot9+27=\\\\=x^3-15x^2+75x-125+x^3+9x^2+27x+27=\\\\=x^3-15x^2+75x-125+x^3+9x^2+27x+27=2x^3-6x^2+102x-98[/tex]

[tex]b)\ \ (3x-1)^3-(2x+1)^3=\\\\=(3x)^3-3\cdot(3x)^2\cdot1+3\cdot3x\cdot1^2-1^3-((2x)^3+3\cdot(2x)^2\cdot1+3\cdot2x\cdot1^2+1^3)=\\\\=27x^3-3\cdot9x^2\cdot1+9x\cdot1-1-(8x^3+3\cdot4x^2\cdot1+6x\cdot1+1)=\\\\=27x^3-27x^2+9x-1-(8x^3+12x^2+6x+1)=\\\\=27x^3-27x^2+9x-1-8x^3-12x^2-6x-1=19x^3-39x^2+3x-2[/tex]

[tex]c)\ \ (x+\frac{1}{2})^3+(x-\frac{1}{2})^3=\\\\=x^3+3x^2\cdot\frac{1}{2}+3x\cdot(\frac{1}{2})^2+(\frac{1}{2})^3+x^3-3x^2\cdot\frac{1}{2}+3x\cdot(\frac{1}{2})^2-(\frac{1}{2})^3=\\\\=x^3+\frac{3}{2}x^2+3x\cdot\frac{1}{4}+\frac{1}{8}+x^3-\frac{3}{2}x^2+3x\cdot\frac{1}{4}-\frac{1}{8}=\\\\=x^3+\frac{3}{2}x^2+\frac{3}{4}x+\frac{1}{8}+x^3-\frac{3}{2}x^2+\frac{3}{4}x-\frac{1}{8}=2x^3+\frac{3}{4}x+\frac{3}{4}x=2x^3+\frac{6}{4}x=\\\\=2x^3+\frac{3}{2}x[/tex]

[tex]d)\ \ (2x+3)^3-(2x-3)^3=\\\\=(2x)^3+3\cdot(2x)^2\cdot3+3\cdot2x\cdot3^2+3^3-((2x)^3-3\cdot(2x)^2\cdot3+3\cdot2x\cdot3^2-3^3)=\\\\=8x^3+3\cdot4x^2\cdot3+6x\cdot9+27-(8x^3-3\cdot4x^2\cdot3+6x\cdot9-27)=\\\\=8x^3+36x^2+54x+27-(8x^3-36x^2+54x-27)=\\\\=8x^3+36x^2+54x+27-8x^3+36x^2-54x+27=72x^2+54[/tex]